2023
DOI: 10.1001/jamasurg.2022.7989
|View full text |Cite
|
Sign up to set email alerts
|

Management of Hepatocellular Carcinoma

Abstract: ImportanceHepatocellular carcinoma (HCC) is the sixth most common malignancy and fourth leading cause of cancer-related death worldwide. Recent advances in systemic and locoregional therapies have led to changes in many guidelines regarding systemic therapy, as well as the possibility to downstage patients to undergo resection. This review examines the advances in surgical and medical therapies relative to multidisciplinary treatment strategies for HCC.ObservationsHCC is a major health problem worldwide. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(105 citation statements)
references
References 89 publications
0
105
0
Order By: Relevance
“…6,7 Other risk factors include hepatitis B virus (HBV), alcohol use, metabolic dysfunction associated steatotic liver disease (MASLD), genetic hemochromatosis, autoimmune hepatitis, primary biliary cholangitis (PBC), aflatoxin B1, tobacco use, and dietary factors. [8][9][10] In addition, recent research led by Reddy et al has identified additional risk factors for HCC, including age, obesity, and a family history of liver cancer with odd ratios of 1.17 (95% confidence interval [CI]; 1.03-1.33), 1.7 (95% CI; 1.08-2.73), and 2.69 (95% CI; 1.11-5.86), respectively. 11 While over 90% of cases of HCC occur in the setting of chronic liver disease, cases can occur in the setting of HBV or MASLD without cirrhosis.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…6,7 Other risk factors include hepatitis B virus (HBV), alcohol use, metabolic dysfunction associated steatotic liver disease (MASLD), genetic hemochromatosis, autoimmune hepatitis, primary biliary cholangitis (PBC), aflatoxin B1, tobacco use, and dietary factors. [8][9][10] In addition, recent research led by Reddy et al has identified additional risk factors for HCC, including age, obesity, and a family history of liver cancer with odd ratios of 1.17 (95% confidence interval [CI]; 1.03-1.33), 1.7 (95% CI; 1.08-2.73), and 2.69 (95% CI; 1.11-5.86), respectively. 11 While over 90% of cases of HCC occur in the setting of chronic liver disease, cases can occur in the setting of HBV or MASLD without cirrhosis.…”
Section: Risk Factorsmentioning
confidence: 99%
“…30 It is recommended that ultrasound imaging for HCC surveillance report a US-LIRADS (Liver Imaging Reporting and Data System) visualization score (from A to C) to help describe the sensitivity of the imaging test and this information should be used in conjunction with the US-LIRADS category (from 1 to 3) and patient factors to determine next steps. 31 Table 1 Odds ratios for hepatocellular carcinoma risk factors 9,10 Other imaging modalities, such as computed tomography (CT) or magnetic resonance imaging (MRI), have been considered as alternatives; however, their routine use is limited by costs, accessibility, and potential harms, such as radiation or contrast exposure. 32 In a prospective study of patients with cirrhosis, the majority of patients with hepatitis B (70.8%), surveillance with MRI with liver-specific contrast allowed for earlier detection of HCC compared with ultrasound.…”
Section: Imaging Modalitymentioning
confidence: 99%
“…Hepatocellular carcinoma (hepatoma) is the sixth-most common cancer worldwide, with an extremely poor prognosis. [1] External beam radiotherapy and transarterial radioembolization are commonly used in patients unable to undergo resection or transplantation. [2] However, its effectiveness in larger tumors is limited by the radiosensitivity of normal tissue, including the liver and small bowel.…”
Section: Introductionmentioning
confidence: 99%
“…1 Due to the high occurrence of metastasis and recurrence of HCC, limited efficacy of radiotherapy and chemotherapy for the majority of HCC patients, and surgical treatment limited to early tumor stages, the underlying mechanism of HCC is urgently needed to be determined for the effective treatment of HCC. [2][3][4][5] Ferroptosis, a metabolism-related and regulated cell death, predominantly brought on by intracellular iron catalytic activity and lipid peroxidation, is defined by intracellular lipid peroxide accumulation and redox imbalance. [6][7][8][9] Ferroptosis is involved in some degenerative diseases, various kidney diseases, liver diseases, brain injury, and stroke as a stress response.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignant tumor entities, ranking sixth in incidence and third in mortality worldwide 1 . Due to the high occurrence of metastasis and recurrence of HCC, limited efficacy of radiotherapy and chemotherapy for the majority of HCC patients, and surgical treatment limited to early tumor stages, the underlying mechanism of HCC is urgently needed to be determined for the effective treatment of HCC 2–5 …”
Section: Introductionmentioning
confidence: 99%